Our voices matter: Young black women’s experiences of identity formation within higher education - Shona Dionne Francis (Fields, 2021)
In today’s social context and Higher Education (HE), a disproportionate number of Black students experience alienation, discrimination and sense of ‘otherness’ because of the racial and/or ethnic identity to which they belong. The intersection of their racial and gendered identity is potentially and undoubtedly influencing their university experiences more generally – positively and negatively. Kimberlé Crenshaw asserts that Black women are more likely than any other ethnic and gendered group to experience double jeopardy and oppression because of this dual identity. The voices of those that belong to this intersectional group remain under-researched within the UK context. Using a qualitative approach and a case study and phenomenological strategy this study explores whether the intersections of race and gender identities can influence educational experiences. It also explores the factors that have contributed to the overall educational experiences of Black women. Data was gathered from four Black students from a university in the North of England, using semi-structured interviews via Skype. The research revealed that race was a salient identity that influencing and had the potential to influence their university experience, more so than gender. It also revealed the racial obstacles and challenges that have influenced their university experience as a Black learner and as a Black woman.